دراسة وتحسين تسطح ربح مضخم رامان متعدد المضخات من أجل عرض حزمة 90nm - هديل عيسى; نغم عباس (Tishreen University, 2018)
تعتمد شبكات الاتصالات الضوئية الحديثة على تقنية التجميع بتقسيم طول الموجة (Wavelength Division Multiplexing (WDM))، حيث كان لابد من العمل على تطوير كامل عناصر الشبكة لتواكب الحاجة المتزايدة لعرض حزمة عريض وتأخير زمني قليل وموثوقية عالية. والاستعاضة عن التجهيزات الإلكترو -ضوئية بالتجهيزات الضوئية بشكل كامل، وأخذت المضخمات الضوئية محوراً هاماً في هذا التطور، وكان لمضخم رامان (RAMAN) حيزاً  كبيراً من الاهتمام لما يقدمه من ربح عالي وتسطح ربح كبير. ركزنا في هذه المقالة على دراسة تأثير كل من بارامترات الليف، وبارامترات المضخة، على أداء مضخم رامان الضوئي من حيث ربحه وعرض الحزمة واستطاعة المضخة المستخدمة. كما بينا تأثير تعدد المضخات على أداء هذا المضخم وعلى تسطح ربحه وعرض الحزمة، وتوصلنا إلى تسطح ربح على عرض حزمة واسع. تمت المحاكاة باستخدام برنامجي MATLAB وOPTISYSTEM بالاعتماد على المعادلات الرياضية التي تصف نموذج المضخم من اجل عرض حزمة 1450nm -1650nm. Modern and future optical networks rely on wavelength divisional multiplexing technology, it was necessary to developed the whole network elements to keep up with the increasing need to offer a wide band and a very short time delay and high reliability, and replacement of electro optic equipment with optical equipment.Optical amplifiers have taken an important part in this evolution, and the Raman amplifier (RAMAN) had a great deal of attention, for its high gain and flattened gain. In this paper, we have examined the effect of both fiber parameters and pump parameters on the performance of Raman optical amplifier in terms of gain and bandwidth and the  used  pump power. This research demonstrated the effect of multi pump on this amplifier performance and its flattening and bandwidth, and we reached a flattening gain on a wide bandwidth. The simulation was done by using MATLAB and OPTISYSTEM program based on the mathematical equations that describe the amplifier model for 1450nm-1650nm bandwidth.